Dual‐edge triggered JK flip‐flop with comprehensive analysis in quantum‐dot cellular automata. Issue 7 (21st May 2018) - Zhang, Yongqiang; Xie, Guangjun; Lv, Hongjun
Abstract : Quantum‐dot cellular automata (QCA), a new computing paradigm at nanoscale, may be a prospective substitution of conventional complementary metal oxide semiconductor (CMOS)‐based integrated circuits. A new dual‐edge triggered JK flip‐flop based on a novel dual‐edge triggered structure with less fundamental building gates is proposed in QCA domain in this study. To get a more robust triggered structure, the probabilistic transfer matrix is employed to analyse the reliability of the structure. The functionalities of the dual‐edge triggered structure and JK flip‐flop are verified with QCADesigner, a simulation tool widely used. By arranging the clock zones serially and QCA cells logically, compared with previous circuits, both of the proposed triggered structure and JK flip‐flop perform well in terms of cells count, area, complexity, QCA cost and power dissipation at different tunnelling energy levels at 2 K temperature, respectively.